The Sistem Informasi Penjualan Air Galon Berbasis Web: Sistem Informasi Penjualan Air Galon Berbasis Web - Tsalisa Ahmad Salaf Syukron Suripah (JETI (Jurnal Elektro dan Teknologi Informasi), 2023)
Abstract- This research discusses the development of a web-based Gallon Water Sales Information System using the waterfall researchmethod. The main focus of this research lies in the planning and maintenance stages of the system in order to achieve responsiveness,efficiency and user satisfaction. At the planning stage, identification of user needs and system objectives is carried out in detail, with carefulneeds analysis to ensure that user and business owner expectations are met. The design phase involves designing the system architecture,user interface, and database structure, providing a holistic view of the system's operations and interactions with users. System implementationis carried out in accordance with predetermined specifications, ensuring that the program code is implemented properly and in accordancewith previous designs. Thorough system testing is carried out to ensure functions are running properly. The test results show that thepercentage of usefulness, ease of use and user interface is 91.6%, making the use of this system very feasible. Expert validators demonstrateda 100% success rate, with a 0% failure rate, confirming that the system performs according to functionality and expectations. The systemmaintenance stage is carried out to ensure operational continuity and adapt to changes in the business and technological environment. Inconclusion, the waterfall method provides a clear and organized structure in the development of this web-based Gallon Water SalesInformation System, with the main advantages of strong planning and documentation. The implementation of this method succeeded inproducing a system that is responsive, efficient, and in line with user expectations.